Revelation is a Symbol: Anti-Radicalism of Pluri-Religious Communities According to Jaspers in the Context of Indonesia - Litno Damanik, Erond; Ndona, Yakobus (International Journal of Criminology and Sociology, 2022)
The article aims to explore and discuss the anti-radicalism of pluri-religious communities in the context of Indonesia. The study is motivated by the high phenomenon of religious radicalism in the last two decades (2000-2020). Religious radicalism is rooted in the understanding of literal revelations recorded in the sacred document. The problem is focused on the erosion of radical ideology targeting the source, namely the language of revelation. The study was carried out qualitative with philosophical hermeneutical approaches that are used to analyze the problem. Data were pooled from journal articles, research, official government reports, print media, and the internet. The theoretical reference used is Jaspers’ relational existentialism. The study found that the language of revelation is not the absolute truth nor the original voice of transcendence, but rather the chiffer who has the role of echoing transcendence. Radicalism is a reflection of narrow and shallow fanaticism, a single truth-based belief over literary revelation. The study concludes that the fundamental anti-radicalism movement in pluri-religious societies is the transposition from literal revelation to symbolic revelation. Novelty studies that the metaphysical-figurative interpretation of literal revelation is necessary to ward off the threat of radicalism.